Science Teachers' Perceptions of Web-Based Learning - Fanny Rahmatina Rahim; Silvi Yulia Sari; Rahmah Evita Putri; Kurnia Andini; Mutiara Dier (Universitas Pendidikan Ganesha, 2023)
The use of technology-based learning media is a requirement in today's learning process. This is because the world has entered a new phase of technological development in which education plays a role. Technology-based education produces a generation who are technologically literate. As a result, teacher efforts are required to incorporate technology into classroom learning. Web-based learning is one example of a technological application in education. Google Sites was used for web-based learning in this study. The purpose of the study is to analyze the perception of science teachers on the use of Google Sites in the classroom. A descriptive method with a quantitative approach was used in the research. The subjects of the study were science teachers in an Indonesian sub-district. Data collection is use Focus Group Discussion, the teacher was asked for his thoughts or perceptions on using Google Sites in the classroom. The data analysis technique used analysis interactive model technique consists of data collection, data reduction, data display, and conclusions. The result of study found Google Sites, according to the majority of teachers, can be used as a website-based learning media. Google Sites meets the six basic indicators of good media ratings, according to teachers. The six indicators are the media's suitability for learning objectives, the accuracy of supporting facts, concepts, and principles in lesson content, the practicality, flexibility, and durability of use, teachers' skills in using Google Sites, target media users, and technical quality.